(untitled) (African Journal of Biomedical Research, 2021)
Free radical-induced cellular damage accelerates ageing. The WHO anticipated that 22% of the population will be over 60years by the year 2050 and 80% of those will live in low-and-middle-income countries (LMIC). It is, therefore, paramount to find local and readily available compounds that could reduce age-induced burden in LMIC. The methanol fruit extract of Ananas sativa and its fractions were evaluated for anti-ageing activity in the fruit fly, Drosophila melanogaster w1118 flies. Experimental flies were fed on food supplemented with 5, 10, and 20mg/ml methanolic fruit pulp-juice extract, lifespan, reproduction, learning, memory and stress resistance assays were evaluated. Phytochemical and the percentage inhibition of the fruit extract on 2, 2-diphenyl-1-picrylhydrazyl free radical (DPPH) were evaluated. Successive bioassay-guided fractionation was used to elucidate the fraction with higher bioactivity. There was a dose-dependent effect, significant at 20mg/ml of extract on lifespan, fertility and oxidative stress resistance (p < 0.05), but not on learning and memory (Tukey’s post hoc test, n =50 flies/group). Male and female % mean survival time were 6.3±0.7, 4.5±1.4 and 13.6±0.5%, and 4.3±0.4, 12.5±0.4 and 20.7±0.4% respectively. The IC50 value of the extract on DPPH was only three times that of Vitamin C, a known pure antioxidant. The Ethyl Acetate fraction increased stress resistance (p < 0.05), but the sub-fractions obtained did not show any anti-ageing activity at the concentrations tested. The methanol fruit extract of Ananas sativa possesses anti-ageing bioactivity through oxidative stress resistance in Drosophila melanogaster w1118 flies